Islam and human rights in the Muslim World: Essentialist and socio-historical perspectives - Didi Jubaidi; Khoirunisa Khoirunnisa (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
The discourse on human rights in the Muslim world continues to generate significant debate, particularly regarding the interplay between Islamic principles and universal human rights standards. This study explores the implementation of human rights in Muslim-majority countries by examining two essential approaches: the essentialist perspective, which views Islamic teachings as inherently compatible with human rights, and the socio-historical perspective, which emphasizes the contextual interpretation of Islamic values in contemporary settings. The research aims to analyze how these differing approaches influence the realization of human rights in the Muslim world. Using qualitative methods, including literature review and content analysis of key Islamic texts, legal frameworks, and case studies from various Muslim countries, the study identifies patterns and challenges in harmonizing Islamic doctrines with global human rights norms. The findings reveal that while the essentialist approach promotes a timeless and unchanging view of human rights within Islam, the socio-historical perspective offers flexibility, allowing for reinterpretation in response to evolving societal needs. The study concludes that a balanced integration of both approaches is essential for fostering a comprehensive and culturally relevant human rights framework in the Muslim world, emphasizing the importance of dialogue, contextual understanding, and legal reforms.